2022
DOI: 10.7717/peerj.13480
|View full text |Cite
|
Sign up to set email alerts
|

The needs of cancer patients during the COVID-19 pandemic—psychosocial, ethical and spiritual aspects—systematic review

Abstract: The COVID-19 pandemic resulted in unprecedented changes in the functioning of the health care system, which were connected with the occurrence of new challenges for both the health care system’s employees and for the patients. The purpose of the present article is to analyze the needs of persons with oncological diseases. Taking into account the multiple aspects of the term health, psychological, social, and existential needs of the patients were analyzed. This article is directed mainly at persons who remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Of the 51 included systematic reviews, 14 articles also included a quantitative analysis/meta-analysis with one being individual participant meta-analysis ( Dhada et al, 2021 ; Teglia et al, 2022a ; Teglia et al, 2022b ; Nikolopoulos et al, 2022 ; Zhang et al, 2022 ; Kirby et al, 2022 ; Donkor et al, 2021 ; Gascon et al, 2022 ; Hojaij et al, 2020 ; Legge et al, 2022 ; Murphy et al, 2022 ; Gadsden et al, 2022 ; Majeed et al, 2022 ; Adham et al, 2022 ; Alom et al, 2021 ; Ayubi et al, 2021 ; Garg et al, 2020 ; Jammu et al, 2021 ; Lu et al, 2021 ; Momenimovahed et al, 2021 ; Mostafaei et al, 2022 ; Moujaess et al, 2020 ; Muls et al, 2022 ; Pacheco et al, 2021 ; Rohilla et al, 2021 ; Salehi et al, 2022 ; Sun et al, 2021 ; Zapała et al, 2022 ; Alkatout et al, 2021 ; Di Cosimo et al, 2022 ; Fancellu et al, 2022 ; Ferrara et al, 2022 ; Hesary and Salehiniya, 2022 ; Lignou et al, 2022 ; Mayo et al, 2021 ; Mazidimoradi et al, 2021 ; Mazidimoradi et al, 2022 ; Ng and Hamilton, 2022 ; Pararas et al, 2022 ; Riera et al, 2021 ; Sarich et al, 2022 ; Sasidharanpillai and Ravishankar, 2022 ; Tang et al, 2022 ; Thomson et al, 2020 ; Vigliar et al, 2020 ; de Bock et al, 2022 ). Other key characteristics of the 51 systematic reviews are shown in Table 1 (more extensive details appear in Supplementary file 1a and Supplementary file 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 51 included systematic reviews, 14 articles also included a quantitative analysis/meta-analysis with one being individual participant meta-analysis ( Dhada et al, 2021 ; Teglia et al, 2022a ; Teglia et al, 2022b ; Nikolopoulos et al, 2022 ; Zhang et al, 2022 ; Kirby et al, 2022 ; Donkor et al, 2021 ; Gascon et al, 2022 ; Hojaij et al, 2020 ; Legge et al, 2022 ; Murphy et al, 2022 ; Gadsden et al, 2022 ; Majeed et al, 2022 ; Adham et al, 2022 ; Alom et al, 2021 ; Ayubi et al, 2021 ; Garg et al, 2020 ; Jammu et al, 2021 ; Lu et al, 2021 ; Momenimovahed et al, 2021 ; Mostafaei et al, 2022 ; Moujaess et al, 2020 ; Muls et al, 2022 ; Pacheco et al, 2021 ; Rohilla et al, 2021 ; Salehi et al, 2022 ; Sun et al, 2021 ; Zapała et al, 2022 ; Alkatout et al, 2021 ; Di Cosimo et al, 2022 ; Fancellu et al, 2022 ; Ferrara et al, 2022 ; Hesary and Salehiniya, 2022 ; Lignou et al, 2022 ; Mayo et al, 2021 ; Mazidimoradi et al, 2021 ; Mazidimoradi et al, 2022 ; Ng and Hamilton, 2022 ; Pararas et al, 2022 ; Riera et al, 2021 ; Sarich et al, 2022 ; Sasidharanpillai and Ravishankar, 2022 ; Tang et al, 2022 ; Thomson et al, 2020 ; Vigliar et al, 2020 ; de Bock et al, 2022 ). Other key characteristics of the 51 systematic reviews are shown in Table 1 (more extensive details appear in Supplementary file 1a and Supplementary file 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary file 1d and Table 4 summarize the main findings from the 15 reviewes ( Dhada et al, 2021 ; Teglia et al, 2022b ; Nikolopoulos et al, 2022 ; Gadsden et al, 2022 ; Majeed et al, 2022 ; Jammu et al, 2021 ; Pacheco et al, 2021 ; Zapała et al, 2022 ; Di Cosimo et al, 2022 ; Ferrara et al, 2022 ; Lignou et al, 2022 ; Mazidimoradi et al, 2021 ; Riera et al, 2021 ; de Bock et al, 2022 ; Piras et al, 2022 ) that assessed and reported on treatment delays and cancellations of cancer treatment. Most reviews mentioned that cancellations of treatment were observed, although to what extend this happened was not consistently provided ( Jammu et al, 2021 ; Pacheco et al, 2021 ; Zapała et al, 2022 ; Di Cosimo et al, 2022 ; Ferrara et al, 2022 ; Mazidimoradi et al, 2021 ; Riera et al, 2021 ). However, reviews reported that these reductions were more pronounced during a lockdown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pandemic has significantly complicated and hindered the process of identifying and adequately responding to the needs of cancer patients. Consequently, it has exacerbated the suffering of patients and their relatives [ 54 ]. Therefore, the activities we conducted responded to the needs of patients and resulted in improved satisfaction with daily life activities and assessment of overall health ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%